Evaluation of The Nutritional Quality of Kuli-kuli (Peanut cake) Produced from Melon seeds and Groundnut. - Achimugu, Solomon; Okolo, Judith (Indonesian Food Science and Technology Journal, 2020)
In the bid to enhance human health and secure food safety as well as public health enlightenment to food, there is the need to evaluate the Nutritional quality of Kuli-kuli from melon seeds. Kuli-kuli which is majorly produced from groundnut is one of the major snacks consumed by most Nigerians especially in the North.The use of melon seeds in the production of Kuli-kuli is not known. Therefore, this research work was carriedout to produce and evaluate the nutrient of Kuli-kuli produced from Melon seeds. Sensory evaluation showed that the Kuli-kuli produced from melon seeds varied in appearance, aroma, texture, taste, and acceptability.